Stairway to Heaven, Cosmos, and Life: A Journey from Mythology to Reality - Belay Sitotaw Goshu; Muhammad Ridwan (Lakhomi Journal Scientific Journal of Culture, 2026)
This review examines the intersection of cultural mythology, cosmological science, and existential philosophy through the lens of Led Zeppelin's iconic song "Stairway to Heaven" (1971). The song's central metaphor a stairway purchased by a woman who believes "all that glitters is gold" serves as a cultural touchstone for exploring humanity's quest for transcendence. Drawing on astrobiology, cosmology, and meaning-centered psychology, this review argues that while the cosmos lacks intrinsic purpose, the very conditions that enable life emerge from cosmic evolution, and meaning can be constructed through conscious engagement with existence. The review synthesizes scientific evidence on the origin of biogenic elements, cosmological constraints on life's emergence, and philosophical frameworks for meaning-making in a purposeless universe.